ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb), KADMIUM (Cd) DAN MERKURI (Hg) DALAM CUMI-CUMI (Loligo Sp.) YANG DIPEROLEH DARI TPI TAMBAK LOROK SEMARANG - aqnes budiarti; rosmini rosmini; henna rya sunoko (Universitas Wahid Hasyim Semarang, 2008)
ABSTRACTThe research about analysis of heavy metal lead (Pb), cadmium (Cd) and mercury (Hg) in Octopuses (Loligo sp.) obtained from TPI Tambak Lorok Semarang has been carried out. This research was intended to identify heavy metals accumulating in octopuses (Loligo sp). The objects studied in this research were octopuses obtained from Tambak Lorok marketplace in Semarang. The sample for this research was taken by simple random sampling at three different points of locations. The locations 1, 2 and 3 were located each from the west, the north and the east, respectively, from the port. The contents of lead, cadmium and mercury in the octopuses’ bodies were measured using SSA (Atom-Absorption Spectrophotometer). The obtained data were then tested using One-way anava. The differences in metal contents were analyzed using Scheffe’s tests and then compared with the basic quality standard stipulated in the Decision Number 03725/B/SK/VII/1989 by the POM Directorate General The study based on the three different points of locations showed the following results. The average lead contents in the octopuses obtained from the points of locations 1, 2 and 3 were 0.29 mg/kg, 0.24 mg/kg and 0.25 mg/kg respectively. The average cadmium contents in the octopuses obtained from the points of locations 1, 2 and 3 were 0.04 mg/kg, 0.05 mg/kg and 0.06 mg/kg respectively. The average mercury contents in the octopuses obtained from the points of locations 1, 2 and 3 were 0.06 mg/kg, 0.07 mg/kg and 0.07 mg/kg respectively The lead, cadmium and mercury contents in the octopuses obtained from the three locations had not exceeded upper limit stipulated in the Decision Number 03725/B/SK/VII/1989 by the POM Directorate General. Based on the One-way ANOVA statistical tests on the lead contents, there was no significant difference among the three samples, but the statistical tests on the cadmium and mercury contents showed a significant difference among the three different points of locations relating to these heavy metal contents in the octopuses Keywords : SSA (Atomic-Absorption Spectrophotometer), Lead (Pb), Cadmium (Cd), Mercury (Hg), Octopuses (Loligo sp), Heavy Metal